New Insights on Hemp Oil Enriched in Cannabidiol: Decarboxylation, Antioxidant Properties and In Vitro Anticancer Effect - Anca Roxana Petrovici; Natalia Simionescu; Andreea Isabela Sandu; Vasile Paraschiv; Mihaela Silion; Mariana Pinteala (MDPI AG, 2021)
This study aimed to obtain and characterize extracted hemp oil enriched in cannabidiol (CBD) by decarboxylation of cannabidiolic acid (CBDA) and to give new insights into its antioxidant and anticancer effects. Optimization of CBDA decarboxylation in hemp oil was performed, and CBD and CBDA contents and purities were determined by flash chromatography, 1H- and 13C-NMR. The antioxidant properties of CBD-enriched oil were investigated by Fe2+ chelating activity, Fe3+ reducing antioxidant power assay, O2●− scavenging activity, HO● scavenging ability and lipid peroxidation inhibitory assay, and its cytotoxicity, apoptosis- and oxidative stress-inducing effects on NHDF, MeWo, HeLa, HepG2 and HOS cells were determined. The CBD concentration in hemp oil was increased by CBDA soft decarboxylation optimized at 90 °C, for 1 h and the resulting oil was capable of reducing iron, scavenging free radicals and inhibiting lipid peroxidation in cell-free oxidative conditions. CBD-enriched oil promoted NHDF proliferation at up to 15 µg CBD/mL, while inducing apoptosis and ROS production and modulating antioxidant enzymes' gene expression in cancer cells, being selective for osteosarcoma cells, and induced apoptosis by p53- and ROS-independent mechanisms. CBD-enriched hemp oil demonstrated antioxidant properties in oxidative conditions and promoted normal fibroblasts' proliferation, while inducing apoptosis and ROS production in cancer cells.